2016
DOI: 10.5812/nmsjournal.39505
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of the Jefferson Scale of Empathy, Nursing Student Version R in a Sample of Iranian Oncology Nurses

Abstract: Background: Empathy is essential in the process of nurse-patient relationships in oncology wards. The lack of a rigorous tool to measure empathy in oncology nurses makes the research difficult. Objectives: Modifying a Persian translation of the Jefferson scale of empathy to create an Iranian version of the Jefferson scale of empathy-nursing student version R (JSE-NS version R), and to determine its validity and reliability in oncology nurses of Tehran Universities of Medical Sciences. Methods: This is a method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…Despite these differences in subscales, from a theoretical point of view, empathy should be considered a system with three elements: CC, PA and Wips. Therefore, empathy is based on the interaction among these elements, an existence characterized mainly by active, positive correlation, and any alteration of their natural relationship (for example, the decrease or absence of positive correlation of an element, such as Wips in our case), may alter the system itself; consequently it cannot function as before or change into another type of system (1,(25)(26) . In others words, empathy is a dialectical synthesis of cognitive (PA and Wips) and affective (CC) attributes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these differences in subscales, from a theoretical point of view, empathy should be considered a system with three elements: CC, PA and Wips. Therefore, empathy is based on the interaction among these elements, an existence characterized mainly by active, positive correlation, and any alteration of their natural relationship (for example, the decrease or absence of positive correlation of an element, such as Wips in our case), may alter the system itself; consequently it cannot function as before or change into another type of system (1,(25)(26) . In others words, empathy is a dialectical synthesis of cognitive (PA and Wips) and affective (CC) attributes.…”
Section: Discussionmentioning
confidence: 99%
“…This is a significant challenge, as it implies profound changes in structure of teaching curricula and its own dynamics right up to the level of empathic teacher training. Many researchers have analyzed studies of interventions for developing empathy in nursing students, concluding that in general, the effect of these interventions on levels of empathy was small to moderate (25)(26)34) .…”
Section: Introductionmentioning
confidence: 99%
“…JSE-NS version R has three factors; "perspective taking" (10 items), "compassionate care" (8 items), and "standing in patient's shoes" (2 items). To calculate the total score, 10 items must be reversed (1,3,(6)(7)(8)(11)(12)(13)(14)(15). The validity and reliability of the Persian version of the JSE-NS version R are confirmed in a previous study (12).…”
Section: Jefferson Scale Of Empathy Nursing Student Version-r (Jse-nsmentioning
confidence: 65%
“…However, in the psychometrics study of the Persian version of this scale, four factors were identified, i.e., "perspective taking", "compassionate care", "standing in patient's shoes", and "metacognitive" (12). The total score ranges from 20 to 140.…”
Section: Jefferson Scale Of Empathy Nursing Student Version-r (Jse-nsmentioning
confidence: 99%
“…One of the strengths of this study is the selection of participants based on the level of empathy from the findings of a previous research [47]. Due to the qualitative data analysis, the generalization of the findings should be done with caution.…”
Section: Discussionmentioning
confidence: 99%